Use of Antibiotics and Probiotic Lactobacilli in the Treatment of Preterm Premature Rupture of Membranes: a Review - Afdanil, Fitra; Suhaimi, Donel; Anggraini, Dewi (Universitas Malahayati, 2024)
ABSTRACT To review the current evidence of the potential use of antibiotics and probiotics Lactobacillus in preterm premature rupture of membranes cases and to see the effect on microorganism concentrations especially Streptococcus agalatiae and Lactobacillus. This review used several databases (Google Scholar, Pubmed, and Science Direct) and searched for English and Indonesian articles in the last ten years. Articles were received in the form of case reports, observational studies and clinical trials that discussed the use of antibiotics and probiotic Lactobacillus in premature rupture of membranes especially in preterm pregnancy. After searching the database and eliminating duplicates and articles unrelated to the topic, we included some articles in this review. Prophylactic antibiotics are also expected to prolong the latent phase, thereby reducing the risk of fetomaternal morbidity and mortality. Penicillin is often recommended in preterm PROM, because broad-spectrum antibiotics are better as infection prophylaxis. Providing alternative therapy with lactobacillus probiotics is believed to prevent preterm birth and has the benefit of being a safe and effective therapy in restoring normal vaginal microflora and preventing vaginal infections during pregnancy. However, further research is needed to see the effectiveness of lactobacillus probiotics and look at the concentration of microbes, especially Streptococcus agalctiae and Lactobacillus. Keywords: Preterm Premature Rupture of Membranes, Antibiotics, Probiotics Lactobacillus, Streptococcus Agalactiae